Sopimusten ja koordinaation merkitys Suomen viljamarkkinoilla - Mäkelä, Saija; Rytsä, Taneli (Maa- ja elintarviketalouden tutkimuskeskus, 2001)
This study analyses the current role of contract production in the Finnish cereal market. Contract production has a long tradition in Finland and has been described as the first step towards a more co-ordinated food chain. In contract production, the farmer and the cereal buyer agree upon the quantity and variety of cereal produced. By using contract production, the supply chain gets a stronger control of quality, quantity and delivery. This study describes some critical points of the cereal supply chain as well as the farmers' motives and incentives for contract production. The goal of the study is to analyse contract production between farmers and cereal buyers. Cereal production in Finland has some special characteristics. Production costs in the cereal production are higher in Finland compared to other EU countries, mainly due to the unfavourable climate conditions. The average yield level is low and the average farm size is quite small (25 hectares). While the average size of farms has increased, the size of base barcel has not increased. The small farm size combined with the distance between arable areas pose great challenges in terms of logistics. The Finnish cereal market is small and concentrated. There are only a few big cereal traders and industrial buyers in the cereal market. Farmers' possibilities to compare different buyers are scarce. In the Finnish cereal market, there are typically two types of business orientations: logistic alliances where trade is organised by cereal traders or partnership between farmers and industrial buyers. The main problems of contract production are risk and uncertainty. Especially in Finland, risks of unstable production levels induced by climate cause difficulties in fulfilling agreed contracts. The data given in this study is obtained from the bookkeeping data of farms participating in the Farm Accountancy Data Network (FADN) and survey based on questionnaires given to farmers. Price determination in advance is important especially for bread grain and malt barley farmers. A year is regarded as an appropriate length of contract period for all cereals. The most important incentive for farmers is the premium structure. Also, the relationship between the ordinary price and incentives play a crucial role. The basic problems for Finnish farmers are low yields and high production costs. The main concerns of cereal traders and industrial buyers are price risk as well as quality and quantity control. Due to low cereal prices, there might be a serious threat that farmers have no incentives to produce quality cereals required by processors. By means of tighter co-ordination, it might be possible to quarantee consistent quality of cereals. With tighter co-ordination in all levels, contract production secures the marketing channel for cereals. Alternative market-channels are open-market systems, which are organised for example via the Internet. Contract production is one way to reinforce co-ordination between farmers and cereal buyers. The main challenge is to solve the motivation problem between participants. It can be solved by means of effective incentives and optimal contract design.
Keywords: Ma; viljamarkkinat; tarjontaketju; sopimukset; kannustin; cereal market; supply chain; contracts; incentives